Reactivity of Thermal Decomposition Products of Ammonium MetavanadateTowards Sodium Sulfate at Different Temperature - F.R. Fouda, Mohammad; I. Saleh, Hasham; M. Abd-Elzaher, Mokhles (Asian Journal of Chemistry, 2010)
The present study is devoted to throw some light on the probable interactions between ammonium metavanadate and sodium sulfite which may help in preparation of vanadium-containing catalyst used in sulfuric acid industry. The probable interactions are in fact chemical reactions between the resulted reactive decomposition products of both salts. The reactive species produced from ammonium metavanadate are (NH4)4 V6O17·l4H2O and V2O5 whereas those produced from sodium sulfite are Na2S5O16, Na2O, Na2SO4 and Na2S. The crystalline reaction products produced at different temperatures are Na2V6O16·3H2O, V2S3, NaV6O15, NaV3O8 and Na8V24O63. The factors which affect the formation and quantities of different products are discussed with the help of the results obtained from X-ray diffraction, electronic absorption spectra, thermogravimetric and chemicals analyses.